Efektivitas Pemungutan Pajak Hiburan pada Badan Pengelola Pajak Dan Retribusi - Nancy Mayriski Siregar (Jurnal Riset AKuntansi dan Bisnis, 2021)
The identification of problems in this study is the lack of compliance of taxpayers in carrying out their virgin obligations in the Binjai City Tax and Levy Management Agency, as well as the lack of quality of tax apparatus in tax collection in the Binjai City Tax and Levy Management Agency. The purpose of this study is to analyze taxpayer compliance and the quality of the tax apparatus, especially entertainment taxes on the Binjai City Tax and Levy Management Agency. The method that the author uses is a descriptive analysis method, where descriptive analysis is a method that seeks to collect data that corresponds to the actual circumstances, presenting and analyzing it so as to provide information in making all decisions. Based on the results of the research, it can be concluded that the collection of entertainment taxes on the Binjai City Tax and Levy Management Agency has not been quite good. This can be seen from the compliance of taxpayers in carrying out their virgin obligations and the quality of the tax apparatus that is not good enough. This can be seen from the low number of taxpayers who report tax returns, especially entertainment taxes.